2019
DOI: 10.1016/j.polymer.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Alkali metal cation adduct effect on polybutylene adipate oligomers: Ion mobility-mass spectrometry

Abstract: Polyurethane (PU) di-block copolymers are one of the most versatile polymeric materials, comprised of hard and soft segments that contribute to PU's broad range of applications. Polybutylene adipate (PBA) is a commonly used soft segment in PU systems. Characterizing the structure of PBA polymers is essential to understanding complex heterogeneity within a PU sample. In this study, ion mobility-mass spectrometry (IM-MS) and tandem mass spectrometry (MS/MS) are used to structurally characterize a PBA standard (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…These DP values can be extracted from the minima of the CCS derivatives, ∂CCS, for each charge state curve of the CCS as a function of the DP (which exhibit at least one structural rearrangement; Table and Figure S14). , The DP half‑rearr can also be evaluated (or verified) using the average DP of the DPs constituting the structural rearrangements, especially if the CCS evolution is slightly disperse and the derivative does not give a single minimum per structural rearrangement.…”
Section: Resultsmentioning
confidence: 99%
“…These DP values can be extracted from the minima of the CCS derivatives, ∂CCS, for each charge state curve of the CCS as a function of the DP (which exhibit at least one structural rearrangement; Table and Figure S14). , The DP half‑rearr can also be evaluated (or verified) using the average DP of the DPs constituting the structural rearrangements, especially if the CCS evolution is slightly disperse and the derivative does not give a single minimum per structural rearrangement.…”
Section: Resultsmentioning
confidence: 99%
“…This was assigned to pendant methyl groups bonded to Si atoms in PDMS, causing a steric hindrance to the chain wrapping around the charges. By plotting the first derivative of CCS (ΔCCS/ΔDP) instead of CCS as a function of DP (such as in Figure c), Hercules and co‐workers clearly highlighted that structural trends observed in IMS‐MS are native to the polymer and independent of the cationization agents . In such a representation (Figure a), the “tipping point” in CCS indicating that a structural transition is achieved corresponds to a valley.…”
Section: Investigation Of Gas‐phase Ion Structuresmentioning
confidence: 99%
“…a, Conceptual illustration of a polymer undergoing charge‐dependent structural transition as indicated by a well‐defined valley while plotting ΔCCS vs DP, and experimental charge state trends observed for polybutylene adipate oligomers with z = +1 (dotted line), z = +2 (dashed line) and z = +3 (solid line) when adducted to b, Li + ; c, Na + ; d, K + ; e, Rb + ; and f, Cs + . Reprinted with permission from Crescentini et al Copyright 2019 Elsevier…”
Section: Investigation Of Gas‐phase Ion Structuresmentioning
confidence: 99%
“…67,68 Although each of these ionization systems has its individual advantages and drawbacks, metal ions have been their main support in the analysis of various polymers by the formation of [M + anion] nÀ and [M + cation] n+ adducts, which led to the improvement of mass spectrometry performance for their analyses. [69][70][71][72][73][74][75][76][77][78][79] It was found that the type and the addition amount of metal salts have pronounced inuences.…”
Section: Metal Salt-assisted Different Ionization Systemsmentioning
confidence: 99%